1979
DOI: 10.1111/j.1471-4159.1979.tb04557.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Levels in Brain Following Experimental Seizures: The Effects of Maximal Electroshock and Phenytoin in Cerebellar Layers

Abstract: Abstract— The effects of maximal electroshock (MES) and phenytoin on metabolites and cyclic nucleotides in layers of frozen‐dried cerebellum have been investigated. The four layers (molecular, Purkinje‐cell rich, granular and white matter) had remarkably homogeneous distributions of P‐creatine, ATP, glucose, glycogen, lactate, GABA and the cyclic nucleotides. MES caused dramatic decreases in P‐creatine, ATP, and glucose at 10 s after treatment, followed by a decrease in glycogen at 30 s. Lactate levels were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
21
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 24 publications
7
21
0
Order By: Relevance
“…The minimal levels were observed 30 sec after MES, while at 10 min glucose increased to greater than normal values. The "overshoot" of glucose had been observed previously in both the cerebellum and cerebral cortex (3,5), and may be attributed to a stress-induced hyperglycemia. The increase in glucose was somewhat greater in the neuropil than in the cell bodies.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The minimal levels were observed 30 sec after MES, while at 10 min glucose increased to greater than normal values. The "overshoot" of glucose had been observed previously in both the cerebellum and cerebral cortex (3,5), and may be attributed to a stress-induced hyperglycemia. The increase in glucose was somewhat greater in the neuropil than in the cell bodies.…”
supporting
confidence: 58%
“…Coincidental with the tonic extension is a reduction of high-energy phosphate compounds in both the cerebellum and cerebral cortex (1-3). Analyses of freeze-dried sections have shown that the changes in energy status are not localized to any one region of the cerebellum, but are comparable in all four layers examined: molecular, Purkinje cell-rich, granular, and white (4). Similarly, the effects of seizures induced by the convulsant isoniazid were comparable in all the cerebral cortical layers examined (5).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[16][17][18]22 Previous studies with microdissection and biochemical assay have revealed increased lactate in microdissected tissue within which Purkinje neurons were the dominant cell type, however, the Purkinje cell layer is too small to isolate without contamination from surrounding tissue (i.e., molecular and granular layer tissue). 22 Therefore, a technique capable of directly imaging the relative lactate concentration at the cellular level (<10 μm spatial resolution) would be of great benefit to this field.…”
Section: 27mentioning
confidence: 99%
“…Quantitative assessment of neuronal loss was confirmed in the pentobarbital experiments by measuring glycogen concentration in the cell body layer (i.e., stratum pyramidale) of the CA1 region. Sections of lyophilized cortex and the CA1 and CA3 cell body layers were dissected, and microquantitative analysis of glycogen content was performed on l-fxg pieces of tissue, as described by McCandless et al 24 …”
Section: Mmentioning
confidence: 99%